The Impact of the (REACT) Strategy Using Small Groups Style on Attention Intensity and Learning Basic Tennis Skills for Students - Khalaf, Hameed; Fayhan, Waleed (Pubmedia Jurnal Pendidikan Olahraga, 2026)
The importance of research lies in reaching the most effective and effective methods and strategies for learners to achieve the best results in the least time and effort, while raising the level of concentration to achieve the desired goal and make playing the game fun. The problem with the research is the answer to the question: Does the REACT strategy contribute to higher attention and learning tennis skills compared to the traditional method? The aim of the research is to identify the effect of the REACT strategy and the strategy followed on the attention acuity and learning of basic tennis skills for students. The researchers used the experimental method according to the design of the two equal groups with pre- and post-tests to suit the nature and problem of the research. The following tests were used to measure the appearance of attention, the transmission accuracy test, and the front and rear ground blow tests. After conducting the scientific basis of the tests, the researchers used the statistical package (SPSS) to process the results statistically and using appropriate statistical methods. After presenting, analyzing and discussing the results, Mal concluded the following: The REACT strategy has a positive and effective role in attention deficit hyperactivity and learning basic tennis skills for the students of the experimental group, the method used has a positive role on attention deficit hyperactivity and learning basic tennis skills for the students of the control group, the experimental group that applied the REACT strategy is superior to the control group that applied the method used in attention acuity and learning basic tennis skills for students.